Answering God's call : finding, following, and fulfilling God's will for your life - Pace, R. Scott (Commendations for Hobbs College Library., 2020)
Biblically insightful, theologically faithful, and practically helpful, Answering God's Call will draw readers into a deeper understanding of God's will for their lives.